Effect of Silica Fume in Combination with Fly Ash on Mortar Properties - Aly Makhlouf (JES: Journal of Engineering Sciences, 2022)
The influence of using silica fume in combination with fly ash on setting time of cement paste and mechanical properties of mortar have been investigated in this paper. Three groups named I, II, and III of mortar include sixteen mixes have been tested in this research work. Mortar specimens cured through keeping them in water until testing day. Initial and final setting times of cement paste were measured. The compression test carried out for mortar at different ages until 180 days, while the flexural strength of mortar measured at 28 days only. The results indicate that the use of silica fume in combination with fly ash as a ternary cementitious material increases the initial and final setting times and improves the measured mechanical properties of mortar. Such combinations offset the problems associated with using increased amounts of fly ash or silica fume required when these materials are used individually. The CO2 emissions from the cement industry will be lowered due to the reduction of the cement content.